Study on the effects of anthocyanins on the growth performance, immunity, and meat quality of ZI geese - He Huang; Size Wang; Chuicheng Zeng; Zhengyu Zang; Yue Pan; Yuanliang Zhang; Shan Yue; JunYing Wang; Peng Zheng; Xiuhua Zhao (Journal of Applied Poultry Research)
Summary: Zi goose is an excellent local breed with fast growth, strong disease resistance, and good meat quality in China. Anthocyanins are natural water-soluble pigments with various biological functions such as promoting growth, antioxidation, and immune regulation. However, research on the beneficial effects of anthocyanins on geese is not yet in-depth. The aim of this study is to investigate the effects of anthocyanins on the growth performance, immunity, and meat quality of Zi geese, providing reference for healthy culture of geese. Two hundred 28-day-old healthy geese were randomly divided into 4 groups with 5 replicates in each group and 10 geese per replicate. Anthocyanins (0, 50, 100, and 200 mg/kg) were added to the goose dietary of the control group (CG), the anthocyanin group 1 (AG1), anthocyanin group 2 (AG2), and anthocyanin group 3 (AG3), respectively. The experimental period was 10 weeks. The results showed that anthocyanin decreased the levels of the interleukin-6 and tumor necrosis factor-α, the abdominal fat percentage, the shear force and drip loss of breast muscle, and increased the levels of immunoglobulin M and interleukin-10, the number of blood lymphocytes, the pH24h value and a* value of breast muscle. In conclusion, anthocyanins can improve immunity, and meat quality, while reduce abdominal fat percentage in Zi geese. The optimum additive amount of anthocyanin was 100 mg/kg in Zi goose.